THE IRREGULAR VERB FORMS MASTERY OF JUNIOR HIGH STUDENTS USING RUBIK??S CUBE - Muh. Shofiyuddin (Universitas Islam Nahdlatul Ulama Jepara, 2016)
This paper aims to descibe a concept how to help students master the irregular verb forms. While there are so many students who are getting difficulties in mastering them. It is proposed to be applied for junior high school students. Meanwhile, there are some students like playing Rubik??s cube. Rubik??s is a kind of scramble game that was discovered by Prof. Erno Rubik in 1974 from Hungaria. The writer would like to use the students?? hobby in order to help them master the irregular verb forms. It is assumed that by using their hobby can help them master the forms while enjoying the game. This paper uses experimental research by a control class. The students would be given pre-test before getting treatment and post-test after being treated. The control class students are not able to play Rubik??s cube and the treatment class students are able to play it. The problem of applying this concept is a researcher need to work twice for students who are not able to play Rubik??s cube.